Saving of Power in Wireless Power Transmission System using IR Sensor and Relay - Nitin Kumar Agrawal; Ruby Kumari (International Journal of Engineering and Management Research, 2020)
As all we know that today’s live is not possible for a moment if we think without electricity after our basic needs that are air, water, food, cloth and shelter. Because without it we can not think about our mobility, But it has also many disadvantages because of the transmission of electricity through wire which cause many time sock due to which living thing may get injured or many time they get unexpected death. Hence for establishing the transmission of electricity without hazards today’s world started working on the removal of the net of the wires over the world and this is possible only by transmitting electricity wirelessly. This principle was early given by a charming and mysterious inventor and engineer Nikola Tesla(1891-1898) by inventing Tesla coil. But in wireless electricity transmission, there is a lot of wastage of energy when power is transferred to the load. If there is no loads are available around the receiving antenna(coil), power will be wasted and this is a one of the major disadvantage of this principle. So by using IR Sensor we can save this power from being waste which will allow the antenna to transmit the power only when the objects are available to receive this transmitted power.